Certain Considerations Regarding the Attributions of the Guardianship Court in the Protection of the Individuals - Creţ Daniela Cristina (Journal of Legal Studies, 2019)
The issue of protecting the natural persons has been triggering a lot of interest due to the need for providing them with proper means for this purpose. In Romania, the court of guardianship and family plays an important role in protecting this category of persons, court established as a result of the entering into force of the new Romanian Civil code in 2011. The legal norms distinguish between the prerogatives of this court on the protection of the major persons and its attributions in this matter towards the minors. Further on, it will be analyzed certain prerogatives of the guardianship and family court meant for the minor persons.